Total plate count of commercial pasteurized milk sold by street vendors in Mulyorejo sub-district Surabaya - Lailatul Maghfiroh; A. T. Soelih Estoepangestie; Tri Nurhajati; Nenny Harijani; Mustofa Helmi Effendi; Didik Handijatno (Journal of halal product and research (JPHR), 2021)
Food and nutritional quality of society is one of mine focuses of the government. Milk have complete nutrients but also can be the source food borne disease. The Veterinary Public Health itself has the responsibility to provide guarantees of food safety from animal resources which is called ASUH (safe, healthy, wholesome and halal) to be consumed by society. This study aimed to know the Total Plate Count of commercial pasteurized milk sold by street vendors in Mulyorejo Sub-district Surabaya. The study was conducted from January until February 2018 at the Laboratory of Veterinary Public Health Department, Faculty of Veterinary Medicine, Universitas Airlangga. Thirty samples of commercial pasteurized milk were bought from three street vendors then examined using Pour Plate Method of Total Plate Count. Total Plate Count result showed that the number of bacteria in commercial pasteurized milk sold by street vendors in Mulyorejo Sub-district Surabaya was 1.0 x 104 CFU/ml, that met the National Standard of Indonesia (SNI) 01-3951-1995.